If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -9 = 6x + 6 Reorder the terms: -9 + 9x = 6x + 6 Reorder the terms: -9 + 9x = 6 + 6x Solving -9 + 9x = 6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -9 + 9x + -6x = 6 + 6x + -6x Combine like terms: 9x + -6x = 3x -9 + 3x = 6 + 6x + -6x Combine like terms: 6x + -6x = 0 -9 + 3x = 6 + 0 -9 + 3x = 6 Add '9' to each side of the equation. -9 + 9 + 3x = 6 + 9 Combine like terms: -9 + 9 = 0 0 + 3x = 6 + 9 3x = 6 + 9 Combine like terms: 6 + 9 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| -2x-29=-7(3x-4) | | x^2-10x+90=9 | | -27*-32= | | 19x-13=-103 | | 5x^3+10=40 | | 47*-16= | | 186x-y=10 | | x^3+7=-1 | | 7x^2-x-12= | | x^2-6x=8x+80 | | -14*92= | | 4x+4y+5z= | | -8(n+4)=-14-5n | | 0.50x+30=55 | | x^3+8=133 | | -16*92= | | y=2x+90 | | 3x^3=63 | | 2(m+29)-12=80 | | 7x-27+4x+12=180 | | x^2-x-66=6 | | 5x^3=125 | | x^4+x^2-2x-1=0 | | 42x^2+67x+21= | | 4y+ax=b+8y(x) | | x^3-x-2= | | -11*-24= | | -9x+9y=27 | | 15n+18=-6n+2 | | 2-2n=3(-n+2) | | 3m+8=3(4+m)-4 | | -48+(-13)= |